Pengaruh Karakteristik Komite Audit terhadap Kecurangan Pelaporan Keuangan (Studi Empiris Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Sihotang, Cristina; Gaol, Manatap Berliana Lumban; Manurung, Amran (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The evolution of economic conditions provides many opportunities for corporate fraud. One form of fraud that often occurs on an international scale and in Indonesia is fraudulent financial reporting in manufacturing companies in the food and beverage sub sector. This research aims to determine empirically the influence of independent audit committees, financial expertise and frequency of audit committee meetings on fraudulent financial reporting in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange. The type of research used is quantitative research. The research sample used was a purposive sampling method, where the sample was determined based on certain criteria, totaling 23 companies. The type of data used in this research is secondary data. The data source used is the annual report of each company published on the website www.idx.co.id. The research results show that the independent audit committee has no significant effect on fraudulent financial reporting, while financial expertise and the frequency/number of audit committee meetings partially have a significant effect on fraudulent financial reporting.